TRANSSEXUALIZING PROCESS IN THE STATE OF CEARÁ: POLITICAL HISTORICAL CONTEXT AND ITS CHALLENGES - de Oliveira Silva , Felipe (2022)
To analyze the implementation of the transsexualization process in the State of Ceará, contexts, conditions and challenges. This is a qualitative research with a phenomenological approach. Five strategic subjects (managers and professionals) were chosen with individual depth techniques. The transsexualization process in the State of Ceará was implemented according to the demand of the transgender population, initially general questions related to sexuality. The challenges point to a lack of human and financial resources, vulnerabilities, lack of access and accessibility to health services, ignorance of the transgender population and prejudice in general. The advances in legitimizing the transsexualization process are notorious, but the idea of transsexuality as a pathology and the insertion of the clinic in the facilities of a chiatric hospital can sustain the stigmatization of Trans people. The transsexualization process is guaranteed by public policies in Ceará, but it is a full implementation of actions that are still limited.